Performance Analysis of Diesel Engine Fueled by 2-Ethylhexyl Nitrate Mixed Biodiesel and the Use of XPower Fuel Ionizer with Injection Timing Variations - Daffa Satya Roziqi; Hadromi (Universitas Negeri Semarang, 2024)
Rapid technological developments encourage the use of diesel engines in transportation and industry due to greater efficiency and power. The cetane number is an important indicator of the quality of diesel fuel, where the addition of additives such as 2EHN can increase the cetane number and improve combustion. Tools such as Fuel Ionizers are also developed to improve fuel efficiency through molecular decomposition. This study aims to determine the power, torque, and specific fuel consumption values ​​in the 4D56 diesel engine when using 2EHN as a fuel mixture and the use of Fuel Ionizer. The power value increases by 1.2 Hp with a mixture of 0.4% 2EHN and the use of Fuel Ionizer at the 8ᴼ ATDC Timing Injection setting. The torque value increases by 2 Nm with a mixture of 0.4% 2EHN and the use of Fuel Ionizer at the 9ᴼ ATDC Timing Injection setting. The lowest specific fuel consumption value is 0.000084 Kg/Hph with a mixture of 0.4% 2EHN and the use of Fuel Ionizer at the 8ᴼ ATDC Timing Injection setting